2020
DOI: 10.1515/znc-2019-0229
|View full text |Cite
|
Sign up to set email alerts
|

Bergamot essential oil nanoemulsions: antimicrobial and cytotoxic activity

Abstract: AbstractBergamot essential oil (BEO) is well-known for its food preservation activity, as well as anticancer efficacy. However, the poor BEO water solubility and deriving low bioaccessibility have limited its wider applications. The incorporation in nanoemulsions of BEO and its refined fractions was investigated to enhance its dispersibility in water to promote its antimicrobial activity, tested against Escherichia coli, Lactobacillus del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 73 publications
0
18
0
3
Order By: Relevance
“…They may also serve as preservatives. Antioxidant, anti-inflammatory, local anaesthetic and analgesic effects are other relevant properties [ 99 , 100 ]. Nevertheless, they play an important role in oral hygiene as fragrances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They may also serve as preservatives. Antioxidant, anti-inflammatory, local anaesthetic and analgesic effects are other relevant properties [ 99 , 100 ]. Nevertheless, they play an important role in oral hygiene as fragrances.…”
Section: Discussionmentioning
confidence: 99%
“…Benzyl alcohol is mainly used as a fragrance and preservative [ 114 , 115 ] and only its derivative (2,4-dichlorobenzyl alcohol) is used as a mild oral and pharyngeal antiseptic. Limonene [ 99 , 116 , 117 ], linalool [ 99 , 117 ], citral [ 118 ] and cinnamal (cinnamaldehyde) [ 119 ] exhibit a non-negligible activity against oral pathogenic microorganisms. Geraniol [ 120 ] and anethole [ 121 ] also show some antimicrobial properties.…”
Section: Discussionmentioning
confidence: 99%
“…Ansari et al reported 3-fold higher permeation of LUT loaded in a self-nanoemulsifying drug delivery system (SNEDDS) in rats [ 12 ]. BO is an essential oil of the generally regarded as safe (GRAS) category and is reported to have more cytotoxic potential when formulated in nanoemulsions [ 49 ]. Thus, improved permeation of LUT loaded cationic nanogobules may be detrimental to cancerous cells.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has demonstrated the antimicrobial activity of EO emulsions, for example bergamot EO nanoemulsions reduced E. coli by up to 4·5 log 10 CFU per ml after 5 h (Marchese et al . 2020). Textile challenge tests show that microemulsion‐treated polyester and cotton also possessed good antimicrobial activity, with a complete reduction achieved by both treated fabrics after 24 h for all test bacteria (Fig.…”
Section: Discussionmentioning
confidence: 99%